Beyond support: exploring the dynamic and static biomechanical changes induced by preventive ankle taping: a novel cross-sectional study - María Bravo-Aguilar; Vanesa Abuín-Porras; María Blanco-Morales; Carlos Romero Morales; Jaime Almazán-Polo; Jorge Hugo Villafañe; Lorena Canosa-Carro (PeerJ)
Introduction In sports, 80% of all ankle injuries are sprains of the external compartment. Functional bandages are usually used preventively, specially in individuals with a history of lateral ankle injuries. To this day, the actual benefits of such taping remain unknown as important modifications are introduced in the ankle biomechanics. Objective The aim of the present study is to describe the biomechanical processes underlying these effects, such as modification during stance times, balance, contact surface and maximum and average pressures in the rearfoot, forefoot and midfoot, using a sprain preventive taping for the external ankle compartment. Methods An observational, analytic, cross-sectional study was designed. Data from static and dynamic plantar pressures with a pressure platform and balance data assessed with the Y Balance Test (YBT) were analysed in 50 participants (age = 21.00 ± 2.34 years, weight = 71.11 ± 13.12 kg, height = 1.75 ± 00.9 m, BMI = 22.94 ± 2.50 kg/m2, foot size = 41.60 ± 3.00) with and without preventive functional taping for lateral ankle sprain (LAS). Results A statistically significant decrease in YBT was observed in the taped participants toward anterior (p = 0.001) and posterolateral (p = 0.005) motion. On the static measures at the pressure platform, an increase in peak pressure at the midfoot (p = 0.001), a decrease in the maximum pressure in the forefoot (p = 0.003) and a decrease in the contact surface in the rearfoot (p = 0.003) were recorded. Dynamic measures at the pressure platform analysis showed a statistically significant decrease in contact surface at the rearfoot (p = 0.001), an increase in mean pressure in both the midfoot (p = 0.044) and forefoot (p = 0.001) and a significant decrease in velocity in the forefoot (p = 0.003). Conclusions In conclusion, we observed that ankle taping led to increased peak pressures in the midfoot and decreased maximum pressures in the forefoot, indicating a shift in load distribution within the plantar surface. Simultaneously, a significant reduction in the velocity at the forefoot during dynamic tasks suggests that taping may alter natural gait dynamics, potentially affecting movement efficiency and stride characteristics. In addition, the application of ankle taping significantly altered balance, as evidenced by a decrease of YBT scores anterior and posterolateral directions. Prophylactic taping in patients with no prior history of LAS is not recommended.